Relación entre el estrés y la procrastinación en estudiantes universitarios - Echeandia Rojas, Andrea Cristina (2022)
Currently, young people show stress and procrastination, problematic phenomena for psychological well-being, due to the demands of the environment and educational challenges. The objective of this research is to identify the relationship between stress and procrastination in the academic area in university students. For this purpose, a review of the applied report of the studies carried out in the last 5 years was carried out. Taking into consideration the criteria of the Prisma guide (Pages et al., 2020), a systematic review of the databases was carried out: Ebsco, Scopus, Dialnet, Redalyc and Proquest, to select correlational quantitative research. 10 studies were selected with samples from university educational institutions. The results reveal that 8 studies find a positive and significant correlation between the variables, while 2 investigations find a negative correlation. The different result may be due to factors such as: the relevance of some dimensions of stress or procrastination within the instruments used and the influence of technology. Finally, it is concluded that stress and procrastination maintain a significant impact on the student facing university challenges, however, depending on the temporal, social, family and educational context, their relationship will be evidenced as positive or negative.